ADVERSE EVENT OF DRUG THERAPY (THE FIRST RESULTS OF THE STUDY ACCORDING TO THE PROFILE OUTPATIENT REGISTER) - Yu. V. Lukina; N. A. Dmitrieva; A. V. Zakharova; A. V. Zagrebelnyy; N. P. Kutishenko; S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии)
Adverse events (As) of medicines are becoming a more serious problem of health care and society due to the growth of the pharmaceutical market. Incomplete information about AEs of drug therapy is an important aspect of this problem. The use of the register method is very promising in the study of adverse drug reactions in clinical practice. Aim. To study the AEs of drug therapy in the PROFILE outpatient register. Material and methods. Primary patients (n=1531) were included into the PROFILE outpatient register from January 2011 to August 2015. The median age of patients was 63 (54; 71) years. The registration card of patients and patient questionnaires were used within the register for the database creation. Analysis of retrospective data of the register was fulfilled Results. Various AEs were reported in 223 (14.6%) patients. Total anamnestic information on 301 cases of AEs was collected: 223 cases were recorded once, 63 – twice, 15 – three times. Patients with AEs were older than patients without AEs ((p<0.0001). AEs were registered most frequently in the use of ACE inhibitors and acetylsalicylic acid: an average of 15% of all cases, each. Various allergic reactions and symptoms of gastrointestinal disorders (pain, nausea, vomiting, diarrhea, etc.) were leaders in the structure of AEs. Naturally there were more patients without AEs among those, who did not take medications. Among patients treated with 6 to 10 medications per day, there were 1.5 times more people who had at least one AE (p<0.0001). Conclusion. The use of the register method allows to add information about the safety of various drugs. However, analysis of the prospective data of the PROFILE register looks the most promising for the solution of this problem.